2013
DOI: 10.1002/ente.201200031
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Photovoltaic Properties of Silicon Solar Cells with Different Diameters and Heights of Nanopillars

Abstract: Silicon nanopillars with average diameters from 200 to 900 nm and heights from 0.5 to 3 μm have been successfully fabricated by cesium chloride (CsCl) self‐assembly lithography and dry etching as antireflection layer for solar cells. The antireflection and photovoltaic characteristics for the structures of silicon nanopillars have been researched and show that the reflectivity, photovoltaic conversion efficiency (PCE), and external quantum efficiency (EQE) are greatly influenced by the average diameter and hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Secondly,t he nanopillars were fabricated by using ICP dry etching with the CsCl nanoislands as masks.F inally,t he wafer was soaked in deionized water to remove the residual masks. [20,21] With this method, silicon nanopillars of heights from 0.2 to 0.5 mmw ere successfully fabricated as an antireflection layer for solar cells.…”
Section: Experimental Section Nanopillar Arrays Fabricationmentioning
confidence: 99%
“…Secondly,t he nanopillars were fabricated by using ICP dry etching with the CsCl nanoislands as masks.F inally,t he wafer was soaked in deionized water to remove the residual masks. [20,21] With this method, silicon nanopillars of heights from 0.2 to 0.5 mmw ere successfully fabricated as an antireflection layer for solar cells.…”
Section: Experimental Section Nanopillar Arrays Fabricationmentioning
confidence: 99%
“…Nevertheless, the large lattice (7%) and thermal mismatch (48%) existed between crystal Si and CdS make the direct growth of high-quality CdS thin films on sc-Si substrate be difficult [11,12], especially for the preparation by liquid chemical method such as CBD. Presently two routes are often adopted to abate the mismatches, one is through inserting an intermediate transition layer or layers [13], and the other is by growing Si (CdS) nanostructures on CdS (Si) bulk substrates [14,15], or even by growing Si (CdS) nanostructures on CdS (Si) nanostructures [6,16,17]. Si nanoporous pillar array (Si-NPA) is a Si hierarchical structure characterized by a regular array of micronsized, quasi-identical and nanoporous silicon pillars, and has been proved to be with strong photoluminescence (PL) at room temperature and high light-absorption in wide spectral range [18].…”
Section: Introductionmentioning
confidence: 99%
“…As appropriate nanofabrication methods become more and more available, different fields have started to benefit from the miniaturization of nanopillars: ongoing research has demonstrated the great potential of nanopillars in photonic crystal structures for the control of a broad range light propagation in broad range of novel optoelectronic devices. Replacing micropillars with nanopillars has proven extremely beneficial also in fields such as nanotechnology, bioelectronics, and biosensors, where devices are being made with increasingly smaller features .…”
Section: Introductionmentioning
confidence: 99%